Breech deliveries in OLVG, the Netherlands: A retrospective cohort study of seven years. (May 2020) - Vinkenvleugel, Danniek A.M.; Slutter, Tessa J.; van Rheenen-Flach, Leonie E.; de Sonnaville, Catherine M.W.; Hermsen, Brenda B.; Velzel, Joost; van Pampus, Maria G.
Abstract: Background: The clinical dilemma on the preferred mode of delivery for breech position still exists. Elective caesarean delivery (CD) could be safer for neonates, whereas vaginal breech delivery (VBD) remains a safe option when conducted by an experienced person. Besides successful VBD is beneficial for mothers and subsequent pregnancies. Objectives: To evaluate breech deliveries on mode of delivery, maternal and neonatal outcomes. Study Design: A single center, retrospective, cohort study was performed of women who delivered a singleton fetus in breech position from 32 weeks' gestation onwards from January 2011 to December 2017. Primary outcome measure was mode of delivery defined as an elective CD and planned VBD. Secondary outcome measures were neonatal and maternal outcome. For neonatal outcome, we used neonatal mortality and a composite measure neonatal morbidity. Maternal outcome included maternal mortality and maternal morbidity divided in severe and non-severe complications. We subcategorized for preterm (32 weeks to 37 weeks of gestation) and term pregnancies (from 37 weeks of gestation onwards). Results: 1.774 women delivered a child in breech position, 73 % opted for an elective CD. Of the 484 women that had a planned VBD (preterm 38 % (n = 59), term 26 % (n = 425)) 71 % were successful. Neonatal mortality occurred twice in the VBD cohort. Preterm neonatal morbidity occurred in the elective CD and VBD cohort equally (both 66 %), at term significantly more in the VBD cohort (12 % v 4%, OR 3.2, 95 % CI 2.1–4.8). For the total cohort, severe maternal postpartum complications occurred more often in the elective CD compared to successful VBD (2% v 0.3 %, OR 6.0, 95 % CI 0.80–44.3). Conclusion: A high rate of successful VBD after opting for a planned VBD was found in our center. Nevertheless, compromised neonatal outcome at term was more frequent in the planned VBD group compared to the elective CD group. Severe maternal postpartum complications were more frequent in the elective CD group compared to the VBD group. Future research should focus alternations in the management of breech presentation.